Expression of Chitotriosidase in Macrophages Modulates Atherosclerotic Plaque Formation in Hyperlipidemic Mice - Yap, Jonathan; McCurdy, Sara; Alcala, Martin; Irei, Jason; Garo, Jan; Regan, Whitney; Lee, Bog-Hieu; Kitamoto, Shiro; Boisvert, William A. (Frontiers in Physiology, 2020)
Objective To determine whether overexpression of the chitin degrading enzyme, chitotriosidase (CHIT1), modulates macrophage function and ameliorates atherosclerosis. Approach and Results Using a mouse model that conditionally overexpresses CHIT1 in macrophages (CHIT1-Tg) crossbred with the Ldlr-/- mouse provided us with a means to investigate the effects of CHIT1 overexpression in the context of atherosclerosis. In vitro, CHIT1 overexpression by murine macrophages enhanced protein expression of IL-4, IL-8, and G-CSF by BMDM upon stimulation with a combination of lipopolysaccharide (LPS) and interferon-γ (IFN-γ). Phosphorylation of ERK1/2 and Akt was also down regulated when exposed to the same inflammatory stimuli. Hyperlipidemic, Ldlr-/–CHIT1-Tg (CHIT1-OE) mice were fed a high-fat diet for 12 weeks to study CHIT1 overexpression in atherosclerosis. Although plaque size and lesion area were not affected by CHIT1 overexpression in vivo, the content of hyaluronic acid (HA) and collagen within atherosclerotic plaques of CHIT1-OE mice was significantly greater. Localization of both ECM components was markedly different between groups. Conclusions These data demonstrate that CHIT1 alters cytokine expression and signaling pathways of classically activated macrophages. In vivo, CHIT1 modifies ECM distribution and content in atherosclerotic plaques, both of which are important therapeutic targets.